Frontispiece: Electroshock synthesis of a bifunctional nonprecious multi‐element alloy for alkaline hydrogen oxidation and evolution (EXP2 6/2022). Issue 6 (18th December 2022) - Du, Lijie; Xiong, Hu; Lu, Hongcheng; Yang, Li‐Ming; Liao, Rong‐Zhen; Xia, Bao Yu; You, Bo
Abstract : A facile electric shock method was used to synthesize an efficient, stable and inexpensive NiCoCuMoW bifunctional alloy electrocatalyst for both hydrogen oxidation and evolution. Density functional theory calculations and electrochemical experiments reveal that the multi‐component synergy and plentiful active sites render the NiCoCuMoW superior electrocatalytic performance, rivalling the Pt/C benchmark catalysts.